The Tradition of Indigenous People as a Learning Material of Social Science at Senior High School - Usmaedi Usmaedi; Bunyamin Maftuh; Hamdan Hamdan; Siti Nurbayani K; Puji Siswanto (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Social science learning through the use of local wisdom values is an effort to instil a sense of concern for others, broaden knowledge about the nation's culture, and is part of an effort to minimize the negative impacts of globalization which cannot be avoided. his study aims to explore the traditions of indigenous communities as teaching materials for high school social studies in the Kasepuhan Adat Cibadak village - Lebak. This study uses a qualitative method and a phenomenological approach. The participants of this study are traditional leaders (Kasepuhan) and members of the indigenous people who live in Kasepuhan Adat Cibadak. The data were obtained from interview, observation and documentation. Based on the results of the data findings, the study reveals that there are well-maintained traditions in this area such as Kabendon, Sedekah Bumi, Ujungan, Mapag pare nyiram, and pantangan. These traditions of indigenous people in Kasepuhan adat Cibadak Warungbanten can be used as materials or sources of social science learning. Therefore, Social Science teachers should think creatively in presenting teaching materials for Social Science subjects at schools.